A study of citizen journalism practices in the Kingdom of Bahrain: insights from the social responsibility theory and news verification tools - Aman, Zahra; Elgammal, Naglaa Abdel Hamid; Fawzy, Hala Elalfy; Kzar, Mazin Hadi; Braimoh, Jimoh Junior (Frontiers in Communication, 2026)
This study aims to investigate to what extent citizen journalists in the Kingdom of Bahrain comply with social responsibility code by adhering to the media law and legislation in Bahrain. This investigation is done using news verification tools as a variable. The methodological framework of the research relies upon a survey of a sample of 132 citizen journalists carried out from January 1 to March 28, 2025. Three research findings emerged. First, two key pillars need to be emphasized for the success of citizen journalism in the Kingdom of Bahrain. These two pillars which are raising awareness of media laws and regulations and fostering a sense of social responsibility are viewed to be capable of leading to increased verification of news before publication, making citizen journalism an effective tool in societal engineering and avoiding sensationalism at the expense of credibility. Second, there is the need to adopt professional ethical guidelines to fit the specific context of citizen journalism. Third, the imperative of organizing educational initiatives and outreach programs in order to promote professional ethical practices among citizen journalists cannot be overstressed. These results explain that the essence of establishing citizen journalism in the Kingdom of Bahrain lies in transforming publishing from an available technical act to a responsible standard practice that is subject to the balance of law, ethics, and professional culture.